O uso das características específicas dos meios impressos nas peças publicitárias: um convite à interatividade - Matuck, Maria Aparecida da Silva (2008)
We live in a post-modern world. As such, this world features countless characteristics that can be noticed in the various aspects of the contemporary society. One of them is advertising. Therefore, this work will focus on some of the characteristics of the postmodernity applied to the context of advertising. Objectively, this application is named here as the use of specific characteristics of printed media. This dissertation discusses, thus, the creative strategy that uses the specific characteristics of printed media (newspapers and magazines) in the language of advertising. Specific characteristics are understood as the physical elements of newspaper and magazine support, such as paper grammage, book spine, the staples of a magazine, etc. used in ads. Therefore, this work highlights ads in newspapers and magazines with an unusual format, that is, which go beyond the mainstream format of ads. This creative strategy makes use of several characteristics of post-modernity that are analyzed in the selected corpus, composed by more than a hundred ads. In a certain historical moment, the use of this creative strategy becomes frequent, influenced by several factors that are studied considering the evolution of printed ads in Brazil. Finally, with a methodology that systematizes common aspects in a group of possibilities, a taxonomy that considers the different specifications for the use of newspapers and magazines; the production factors; the creative resources and the exploration of the senses.